1952
DOI: 10.1111/j.1365-2621.1952.tb16765.x
|View full text |Cite
|
Sign up to set email alerts
|

ACID‐TOLERANT BACTERIA IN CITRUS JUICESa

Abstract: Available literature pertaining to the types of bacteria indigenous to citrus juices is very limited. Faville, Hill, and Parish (1) reported that bacteria comprised the majority of organisms isolated from samples of frozen concentrated orange juice and that Leucomostoc was the predominant genus present, while reports on the occurrence of coliform organisms by Patrick ( 6 ) , Wolford and Berry (11,12), and Wolford (10) constitute the remaining publications on this subject.Although the relatively high citric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1955
1955
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This spoilage is usually characterized by a "butter" off-flavor attributed to microbial diacetyl production (Faville and Hill, 1952;Hays and Riester, 1952).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This spoilage is usually characterized by a "butter" off-flavor attributed to microbial diacetyl production (Faville and Hill, 1952;Hays and Riester, 1952).…”
Section: Introductionmentioning
confidence: 99%
“…DUE TO THE ACIDURIC NATURE of lactobacilli and leuconostocs, species of these genera are primarily responsible for bacterial spoilage of citrus juices. This spoilage is usually characterized by a "butter" off-flavor attributed to microbial diacetyl production (Faville and Hill, 1952;Hays and Riester, 1952).…”
Section: Introductionmentioning
confidence: 99%
“…Species which have been reported as isolated from citrus products include: Lactobacillus brevis, L. plantarum, L. thermophilus, Leuconostoc mesenteroides and Le. dtxtranicum (Yanai et al, 1986;Faville and Hill, 1952;Hays and Riester, 1952;Hays, 1951). Based on the microbial identifications from the 195Os, other researchers have conducted various studies on citrus products using either those species of organisms previously identified or other industrially derived strains which are usually identified only to the genus level (Patrick and Hill, 1959).…”
Section: Introductionmentioning
confidence: 95%
“…Hays (1951) demonstrated the presence of Lactobacillus spp. in spoilage outbreaks and Faville & Hill (1952), who studied the growth of acid-tolerant bacteria isolated from fruit and from single strength and concentrated juice, showed the ability of species of Leucomstoc, Lactobacillus, Xanthomonas and Achromobacter to survive or grow at p H levels of 4.0 and below. Ingram (1949, 1950) has shown the importance of yeasts in the spoilage of concentrated orange juice and Recca & Mrak (1952) extended the study of yeasts from the Rhodotorula and Zygosaccharomyces isolated by Ingram to 92 cultures of imperfect and ascospore producing yeasts, of which Candida, Zygosaccharomyces, Hanseniospora, Pichia and Saccharomyw were the most important genera.…”
Section: Microbiology Relative To Spoilage (A) Qeneralmentioning
confidence: 99%